2022
DOI: 10.1097/jom.0000000000002586
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms Are Associated With Decreased Quality of Life and Work Ability in Currently Working Health Care Workers With Recurrent Low Back Pain

Abstract: For health care workers, low back pain (LBP) is one of the leading causes of work disability and early exit from the labor market. Moreover, depressive symptoms are common with LBP, and the treatment of these symptoms is a crucial step in improving the quality of life and work ability of health care workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…We used a short work ability index (sWAI) as the main indicator of WA [ 20 ]. The index includes four questions from the original seven-item Work Ability Index (WAI) [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We used a short work ability index (sWAI) as the main indicator of WA [ 20 ]. The index includes four questions from the original seven-item Work Ability Index (WAI) [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the summary of the sWAI, we also used a single-item question of current WA (work ability score (WAS), range of 1–10) as an indicator of present WA. Previously, the same version of the sWAI has been used among health care workers with recurrent low back pain [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, multisite pain is associated with a greater negative impact on the physical functioning and disability of patients and increases the risk for poor perceived future work ability and lower quality of life [5,[15][16]. In a recent study, recurrent LBP combined with multisite pain or depressive symptoms was reported to have a negative association with quality of life among health care workers [20].…”
Section: Discussionmentioning
confidence: 99%